2020
DOI: 10.1021/acscatal.0c04314
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Cooperativity in CO2 Reduction Using a Xanthene-Bridged Bimetallic Rhenium(I) Complex

Abstract: Mechanistic studies on dinuclear complexes that can activate CO 2 are rare. Based on the investigations done for the mononuclear compound (bpy)Re(CO) 3 Cl (bpy-Re, with bpy = 2,2′-bipyridine), many reports favor a mononuclear catalytic cycle, while the possibility of a dinuclear catalytic species is discussed in the literature in only a few cases. Here, we report the synthesis and characterization of a homobimetallic rhenium(I) compound, in which two (bipyridine)Re(CO) 3 Cl fragments are brought into close vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(89 citation statements)
references
References 85 publications
5
84
0
Order By: Relevance
“…Compound Re 2 Cl 2 was synthesized according to an already published method. [20] As outlined in the introduction, the goal of the recent studies is to achieve an efficient and fast formation of higher reduced species of Re 2 Cl 2 , i. e. [Re 2 Cl 2 ] nÀ . Since the prerequisite for the formation of doubly-reduced Re 2 Cl 2 by an external photosensitizer is a) a high reductive power in the ground-state (c.f.…”
Section: Photocatalytic Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Compound Re 2 Cl 2 was synthesized according to an already published method. [20] As outlined in the introduction, the goal of the recent studies is to achieve an efficient and fast formation of higher reduced species of Re 2 Cl 2 , i. e. [Re 2 Cl 2 ] nÀ . Since the prerequisite for the formation of doubly-reduced Re 2 Cl 2 by an external photosensitizer is a) a high reductive power in the ground-state (c.f.…”
Section: Photocatalytic Studiesmentioning
confidence: 99%
“…Initial studies by us revealed that the accumulation of two electrons on Re 2 Cl 2 by means of photoinduced electron transfer reactions from sacrificial electron donors is hampered by a strong electronic communication between the two metal fragments. [20] However, if the system was reduced twice (e. g. by [a] Ir 200 200 1 154 4 [a] Ir 200 400 1 131 5 [a] Ir 400 200 1 134 6 [a] Ir 400 400 1 193 7 [a] Ir 1 eq. Ir, 5 % TEA; blue: 1 eq.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
See 3 more Smart Citations